Pelatihan Teknologi AQSILER (Aquaponic-Integrating Fish And Plant Culture) untuk Meningkatan Ketahanan Pangan Keluarga di Kelurahan Amen Kabupaten Lebong (Bengkulu) - Dewi Jumiarni; Ahmad Saddam Husein; Teddy Alfra Siagian; Yennita, Yennita; Nursanti Yunita Sari (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2025)
The objective of this community service activity is firstly, to enhance the community's awareness and expertise in the utilisation of AQSILER technology; and secondly, to implement AQSILER technology in order to enhance family food security in Amen Village. The activity was conducted in the village hall of Amen Village, Lebong Regency (Bengkulu), with 30 participants. The methodology employed in this study was Participatory Action Research (PAR), which was meticulously executed in three distinct stages: namely, preparation, training and monitoring and evaluation. The findings of the activity demonstrated that it was effective in enhancing the knowledge and skills of the participants in relation to AQSILER technology by 75%, meeting the highest standards of evaluation. The implementation of AQSILER technology in Amen Village has resulted in the cultivation of kale and catfish, thereby ensuring the sustenance of local households. The harvesting of kale can be initiated after the third week. The subsequent harvest is conducted at two-week intervals. Conversely, catfish are harvested at a younger age, typically between three and five months, depending on the specific requirements of the harvesting operation. It is estimated that 100 catfish seeds will yield 40-60 fish, with a total weight of 8-12 kilograms. Keywords:  AQSILER, aquaponics, food resilience and appropriate technology.